Between Commemoration and Criminalization: Demystifying, Demythologizing, and Debunking the Canadian Police and Peace Officers' Memorial - Ferguson, Matthew (Université d'Ottawa / University of Ottawa, 2023)
While significant scholarly research exists on memorialization and commemoration, little exists on memorials to police officers, prison guards, border agents, and other penal system actors described as "law enforcement" or "peace" officers. This doctoral dissertation helps fill this gap by examining three questions: 1) How is penal system work staged and performed through the dramatic spectacle of national commemoration? 2) How does the memorialization of penal system actors as heroes generate and maintain support for punishment and the social distance between ordinary citizens and individuals in conflict with the law? 3) What myths are constructed and perpetuated through these memorials that legitimize the existence, expansion, and domination of punitive ways of thinking about and responding to criminalized conflict and harms? I explore these questions through a case study of "The Canadian Police and Peace Officers Memorial" (CPPOM) on Parliament Hill in Ottawa, Ontario, Canada through a thematic analysis and thick description of data from over 850 newspaper articles, 40 magazine articles, 19 semi-structured interviews, 18 survey responses, and participant observation at the memorial - including recently created running and cycling events. Rather than just a national day or annual gathering of authorities on the last Sunday in September, I argue that the CPPOM is also an overlooked penal system service, organization, and institution, which is integral to broader and growing attempts by police chiefs and associations, as well as other penal system actors and their families in Canada and the United States, to further expand and entrench penal system practices as central to the Canadian national identity through organizational memories and myths that work to increase support for penal system officers by staging them as prepared, professional, heroic, effective, and united. I reflect on the implications of the findings and future avenues for research on memorials like the CPPOM, whose birth in the late-1970s is shown to stem not simply from the "murder" of a rookie Ottawa police officer as is claimed during the memorial activities today, but also from a lack of preparedness and professionalism in the arrest of the person living with mental illness that led to the death of the rookie officer, as well as other national, local, and structural dilemmas facing penal system actors at the time. In examining and providing a new account of the origins, development, meanings, and role of the CPPOM, I contribute to the demystification, demythologization, and debunking of this national memorial, thus contributing to critical criminology and growing attempts to move beyond the punitive responses it naturalizes and legitimates. Although helping participants heal, connect, and move forward after death - which for some, occurs just one step or pedal stroke at a time - I show how the CPPOM is also a forgetful and misleading performance, which has consistently staged public criticism of policing as unfair and "violent crime" and a perceived lack of respect for police and the law as crises, not of mental illness, addiction, poverty, racism, or the real harms and limitations of policing and punishment themselves, but of a lack of law and order that can only be secured through the further entrenchment of penality and the work of "peace" officers.
Keywords: police memorial; policing; punishment; memorialization; commemoration; penality; monument; penal tourism; Canada